Alcohol use in firefighters: A network model of behaviors and transdiagnostic risk. (1st December 2022) - Karnick, Aleksandr T.; Buerke, Morgan; Caulfied, Nicole; Trussell, Dylan; Capron, Daniel W.; Vujanovic, Anka
Abstract: Background and aims: Firefighters are at heightened risk for developing alcohol use disorder (AUD), possibly due to chronic stress and exposure to potentially traumatic events. Daily trauma experiences and transdiagnostic risk factors (i.e., anxiety sensitivity and distress intolerance) are related to posttraumatic stress and depressive symptoms, as well as alcohol use severity and alcohol as a coping strategy. Although alcohol use has been identified as a key target for addressing mental health in firefighters, prior research has not fully integrated transdiagnostic vulnerabilities, internalizing symptoms, posttraumatic stress symptoms, alcohol coping, and overall alcohol use into a dynamic network model. Methods: We assessed the symptom structure of overall alcohol use in firefighters with a likely AUD and transdiagnostic risk factors in all firefighters using network analysis. Results: Failing to meet expectations (Expected Influence [EI]: 1.32), morning dependence (EI: 1.07), and guilt about drinking (EI: 1.10) were most central to the network model developed for firefighters with a likely AUD. In a transdiagnostic model of use in firefighters overall, anxiety sensitivity cognitive concerns (EI: 1.48) and negative alterations to cognitions and mood related to trauma (EI: 1.87) had the highest influence on the network. Notable correlations were also identified between trauma arousal and overall alcohol use, between depression and alcohol coping motives, and between trauma avoidance and alcohol coping motives. Conclusions: Alcohol use behaviors may follow a unique etiologic pathway in firefighters and intervention strategies should target factors found to be more central to symptom networks. Highlights: First responder networks of alcohol use behaviors and transdiagnostic risk were generated. Failing expectations and guilt were drinking behaviors most central in likely AUD networks. Trauma arousal and overall alcohol use were correlated in the transdiagnostic networks. Depression and alcohol for coping were also correlated in the transdiagnostic networks. First responder interventions should target more influential symptoms in alcohol use networks.